Neutron source reconstruction using a generalized expectation-maximization algorithm on one-dimensional neutron images from the Z facility - Ricketts, S A; Mangan, M A; Volegov, P; Fittinghoff, D N; Lewis, W E; Mannion, O M; Morel, J E; Adams, M L; Ampleford, D J (Review of scientific instruments, 2024)
Magnetized Liner Inertial Fusion experiments have been performed at the Z facility at Sandia National Laboratories. These experiments use deuterium fuel, which produces 2.45 MeV neutrons on reaching thermonuclear conditions. To study the spatial structure of neutron production, the one-dimensional imager of neutrons diagnostic was fielded to record axial resolved neutron images. In this diagnostic, neutrons passing through a rolled edge aperture form an image on a CR-39-based solid state nuclear track detector. Here, we present a modified generalized expectation-maximization algorithm to reconstruct an axial neutron emission profile of the stagnated fusion plasma. We validate the approach by comparing the reconstructed neutron emission profile to an x-ray emission profile provided by a time-integrated pinhole camera.